Chemical compounds, antioxidant and antimicrobial capacity of two methanolic extracts of Agave Angustifolia leaves - López Romero, Julio César; González Ríos, Humberto; Valenzuela Melendres, Martín; Ayala Zavala, Jesús Fernando; Meza Callado, Ana Guadalupe (Ecosistemas y Recursos Agropecuarios, 2023)
Agave angustifolia is a plant used in folk medicine against different health conditions, however, its main use as alcoholic beverages raw material. In this process, the leaves are discarded, representing 50 % of the plant weight, which are considered byproducts. Considering the medicinal purposes, these byproducts could be used for extract obtention by using different methods and determining their biological potential. The objective of this research was to evaluate the content of bioactive compounds, antioxidant and antimicrobial activity of A. angustifolia leaves extract obtained by two extraction methods. Methanolic extracts were performed from A. angustifolia leaves through sonication and soxhlet methods. The content of total phenols, total flavonoids, hydrolyzable, condensed tannins, and saponins were quantified. Antioxidant activity was performed by the DPPH, ABTS, and FRAP methods. Bactericidal activity was evaluated against 10 pathogens using the growth plate method. Generally, the obtained results showed that the extraction method did not affect (p>0.05) the concentration of bioactive compounds. Similar results were obtained in the free radicals scavenged activity (p>0.05). However, the reducing potential was increased by the sonication method. The antimicrobial evaluation showed that the extract obtained by the soxhlet method increased the antimicrobial effect. A. angustifolia is a natural source of bioactive compounds, which, are not modified for the extraction methods tested, however, the biological potential could be affected.